Vaccination with single plasmid DNA encoding IL-12 and antigens of severe fever with thrombocytopenia syndrome virus elicits complete protection in IFNAR knockout mice. - Jun-Gu Kang; Kyeongseok Jeon; Hooncheol Choi; Yuri Kim; Hong-Il Kim; Hyo-Jin Ro; Yong Bok Seo; Jua Shin; Junho Chung; Yoon Kyung Jeon; Yang Soo Kim; Keun Hwa Lee; et al. (Public Library of Science (PLoS), 2020)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne disease caused by SFTS virus (SFTSV) infection. Despite a gradual increase of SFTS cases and high mortality in endemic regions, no specific viral therapy nor vaccine is available. Here, we developed a single recombinant plasmid DNA encoding SFTSV genes, Gn and Gc together with NP-NS fusion antigen, as a vaccine candidate. The viral antigens were fused with Fms-like tyrosine kinase-3 ligand (Flt3L) and IL-12 gene was incorporated into the plasmid to enhance cell-mediated immunity. Vaccination with the DNA provides complete protection of IFNAR KO mice upon lethal SFTSV challenge, whereas immunization with a plasmid without IL-12 gene resulted in partial protection. Since we failed to detect antibodies against surface glycoproteins, Gn and Gc, in the immunized mice, antigen-specific cellular immunity, as confirmed by enhanced antigen-specific T cell responses, might play major role in protection. Finally, we evaluated the degree of protective immunity provided by protein immunization of the individual glycoprotein, Gn or Gc. Although both protein antigens induced a significant level of neutralizing activity against SFTSV, Gn vaccination resulted in relatively higher neutralizing activity and better protection than Gc vaccination. However, both antigens failed to provide complete protection. Given that DNA vaccines have failed to induce sufficient immunogenicity in human trials when compared to protein vaccines, optimal combinations of DNA and protein elements, proper selection of target antigens, and incorporation of efficient adjuvant, need to be further investigated for SFTSV vaccine development.